2008
DOI: 10.1007/s11257-007-9045-6
|View full text |Cite
|
Sign up to set email alerts
|

Developing a generalizable detector of when students game the system

Abstract: Some students, when working in interactive learning environments, attempt to "game the system", attempting to succeed in the environment by exploiting properties of the system rather than by learning the material and trying to use that knowledge to answer correctly. In this paper, we present a system that can accurately detect whether a student is gaming the system, within a Cognitive Tutor mathematics curricula. Our detector also distinguishes between two distinct types of gaming which are associated with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
1
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 20 publications
2
100
1
6
Order By: Relevance
“…[6]). The experimental procedure was as follows: college students with no college-level physics (1) read a short physics text, (2) took a multiple choice pretest, (3) worked with ITSPOKE, (4) took a survey, and (5) took an isomorphic posttest. The resulting corpus contains 360 spoken dialogs (5 per student) from 72 students (6044 student turns).…”
Section: Computer Tutoring Disengagement Datamentioning
confidence: 99%
See 4 more Smart Citations
“…[6]). The experimental procedure was as follows: college students with no college-level physics (1) read a short physics text, (2) took a multiple choice pretest, (3) worked with ITSPOKE, (4) took a survey, and (5) took an isomorphic posttest. The resulting corpus contains 360 spoken dialogs (5 per student) from 72 students (6044 student turns).…”
Section: Computer Tutoring Disengagement Datamentioning
confidence: 99%
“…Student (dis)engagement behaviors have been of particular interest in this research, including displays of gaming, boredom, indifference, (lack of) interest, (low) motivation, curiosity, and flow (e.g. [7,3,9,11,12]). Correlational analyses of student (dis)engagement behaviors in tutoring system corpora have indicated that these behaviors are predictive of learning.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations